Simples nacional: análise de sua estrutura normativa sob os planos da linguagem prescritiva do direito - Brito, Sérgio de Abreu (2013)
The dissertation addresses the Simples Nacional, simplified tax regime for micro and small enterprises, established by Brazilian Supplementary Law n. 123/2006, in order to fulfill the constitutional commandment that provides the favored tax treatment and differential in favor of small economic entities (CF/88, arts. 146, section III, paragraph "d" and sole paragraph 170, section IX and 179). In this regime, taxes are calculated quickly and practical, taking as parameters for calculating the gross revenue of the taxpayer and the percentages set out in annexes of the mentioned complementary law. The main objective of this work is to assess the compatibility of that special regime with the rule constitutional underpinning its creation, as well as those that confer taxing power on the federal entities. To do so, we use a semiotic approach, with entry into the syntactic, semantic and pragmatic plans of prescriptive language of the positive law. From this methodological tool examines the normative structure of the Simples Nacional, building up all the tax rules included in it. With the identification of the criteria of the hypothesis and the consequent of these tax rules, will be able to answer a series of questions pertaining to the simplified taxation scheme under consideration, for example, was altered in material criterion of the hypothesis incidence of some taxes? The gross revenue of opting for Simple National would be the calculation base of all taxes encompassed by this differentiated regime?